RANCANG BANGUN PERALATAN IODISASI GARAM PORTABEL MENGGUNAKAN SISTEM SEMI OTOMATIS (Design and Manufacturing of Portable Salt Iodized Apparatus Using Semi Automatic System) - Mahlinda, Mahlinda; Maurina, Lancy (Jurnal Hasil Penelitian Industri, 2013)
The researches about design and manufacturing of portable salt iodizedapparatus using semi-automatic system have been done. The aim of this research was tostudied and to designed salt iodized apparatus which can be operation automatically tosprayer and mixing salt to be iodized. Result of mechanic and automatic system testingshowed all testing parameters working well and stable. Testing result of iodine contentbased on iodat tester colour showed the best iodine content getting from spayer times 3second with KIO3 volume achieve 27 cc and iodat testing appear old puple colour. Testingresult of iodized salt showed all parameters fulfill with SNI. No. 01-3556-200. Theadvantage of this apparatus were easily to removing, low energy consumption, workingautomatically and easy to maintenance.